Micro-CT characterization on pore structure evolution of low-permeability sandstone under acid treatment - Liu, Sinan; Zhang, Liwei; Su, Xuebin; Zhao, Lixin; Wang, Yan (Applied geochemistry, 2023)
Permeability enhancement via acid has drawn broad attention in mining and oil industries to treat low-permeability formations to increase the resource recovery rate. In this study, experiments including static acid permeability enhancement tests, flooding acid permeability enhancement tests, and micro-CT scanning were conducted to investigate the mechanism of permeability enhancement and changes in pore structure during acid treatment. First, the extent of reaction between low-permeability sandstone samples and four different acids was evaluated by static tests. The hydrochloric and formic acids exhibited good performance to dissolve filling minerals during static tests. Second, acid flooding in sandstone cores was carried out under reservoir conditions. After acid flooding, the porosities of sandstone cores were significantly increased and a decrease in pressure difference was observed, demonstrating a permeability increase. The pressure difference of hydrochloric acids was lower than that of formic acids at the end of flooding, and the permeability results indicated that the percentage of permeability increase by hydrochloric acid treatment and formic acid treatment were 283% and 120%, respectively. Third, all samples were scanned by micro-CT before and after acid permeability enhancement tests, and CT images were analyzed to study changes in pores, pore throats, and coordination numbers using Avizo software. The mineral compositions and 2D micromorphology were characterized by SEM-EDS, XRD and ICP. After acid treatment, the number of interconnected pores, pore throats, and their equivalent radii all increased, leading to a higher permeability. The improved permeability was mainly due to the dissolution of dolomite, which was identified by SEM-EDS and ICP. •CT images reveal the extent of reaction in sandstone samples during static acid reaction tests, showing mineral dissolution.•The preferential dissolution of carbonates in the samples causes preferential flow of acid solution.•After acid treatment, the number of interconnected pores, pore throats, and their equivalent radii all increase.